BIM Application in Infrastructure Projects - Tatjana Vilutienė; Edita Šarkienė; Vaidotas Šarka; Arvydas Kiaulakis (The Baltic Journal of Road and Bridge Engineering)
Building Information Modelling (BIM) is becoming a common language for the construction of buildings and infrastructure sectors worldwide. This paper aims at providing a broad picture of published journal papers on BIM application in infrastructure projects. The review is based on bibliometric analysis of 239 papers. The bibliometric analysis technique is used as the analysis method, which when compared to conventional literature reviews allows for the reduction in the likelihood of subjective judgments. The paper presents the review of BIM applications in infrastructure projects analysed within a 10-year period; the analysis of most recent studies and trends of applying BIM methodology identifies the gaps of BIM applications in infrastructure projects and defines future areas of research. Detailed analyses of citation networks present the co-occurrence map of keywords, citation patterns of journals, articles and the most cited journals in the research area. Research shows that BIM applications in infrastructure projects have been continuously growing with a sudden increase after 2016. The study reveals that the research in this area conducted mainly in isolation comprised disjointed and fragmented research studies. Some of the sources are not available in scientific databases.